IMPACT OF LAPINDO MUD DUMPING WATER IN MADURA STRAIT EAST JAVA - I Insafitri (Jurnal Kelautan, 2009)
Warm water mud has sprayed out from craked of the earth surroundings gasses drilling by Lapindo Brantas Inc in village of Siring, Porong Subdistrict, Sidoarjo Regency, a large industrial zone and the economic backbone of East Java Province, at May 29 2006. The mud water created problems in the environment, relocation of people, conflicts, and controversies on the issue of dumping warm mud water into Porong River and Madura Strait, East Java. In this paper, I reviewed secondary literature to analyze and examine the impacts of dumping mud water in Madura Strait East Java to provide recommendations in the proper management of mud water. Literature provides that the quality of mud water was beyond the standards provided by the State Ministry of Environment Republic Indonesia and International Environment Quality Standard. Temperature is 38 - 56 0C, Hg (Mercury) is 2.5 ppm, H2S Fenol is 3.37-4.25 ppm, BOD is 38.40 mg/L, Manganese is  0.806 ppm, Pb is 0.104 ppm, Selenia is 0.0071 ppm.Water mud of Lapindo drained into the sea endangers biotic organisms. The recommendation are: Spray out of mud water should be stopped and mud water doesn't thrown to sea, Lapindo must make a permanent giant lake to keep mud water in the origin of place, If the previous recommendation cannot done, than for keep the live of man surrounding the area, the water may be trown to the river or sea after the water processing, but the mud must still remaining in the ground, not to thrown in the sea. Keywords: Mud water of Lapindo, Dumping.